Quantitative and qualitative characteristics of the non-carcass components and the meat of lambs fed sunflower seeds and vitamin E - Natália Ludmila Lins Lima; Américo Garcia da Silva Sobrinho; Fabiana Alves de Almeida; Viviane Endo; Nivea Maria Brancacci Lopes Zeola; Amélia Katiane de Almeida; Alexandre Amstalden Moraes Sampaio (Revista Brasileira de Zootecnia, 2013)
The objective of this investigation was to evaluate the weight and percentage of the non-carcass components and the mineral content (macro minerals and trace minerals), crude protein, ether extract, moisture and vitamin E of the heart, liver, tongue, lungs, reticulum, kidneys and meat from the longissimus dorsi of lambs in feedlot finishing. Thirty-two non-castrated Ile de France male lambs, fed diets containing sunflower seeds and vitamin E from 15 to 32 kg of body weight were allotted in a completely randomized design in a 2 × 2 factorial arrangement. The weight of the gastrointestinal tract was higher in the lambs fed diets containing vitamin E (10%). No difference was observed in the liver as to the mineral matter, crude protein, ether extract, moisture (2.01; 20.03; 2.39 and 74.78 g/100 g, respectively), the macro minerals and trace minerals, except iron. In the tongue, lungs, reticulum, kidneys and meat there was no in fluence of diets in the studied variables. The liver and the meat presented different values of crude protein (20.01 and 18.34 g/100 g, respectively), and the heart (1.03 mg/100 g) showed a higher content of vitamin E. High contents of manganese, zinc and copper were observed in the liver. The evaluated non-carcass components were nutritionally equal to the sheep meat, once, in addition to their high yield in relation to the body weight at slaughter, the non-carcass components are sources of nutrients.